Customer awareness of green purchase decisions regarding green products in Nepal - Garima Shrestha; Niranjan Devkota; Krishna Dhakal; Surendra Mahato; Udaya Raj Paudel; Sarita Agrawal (Journal of the Academy of Business and Emerging Markets, 2023)
This study focuses on customer awareness of green marketing and determines consumers’ purchase decisions regarding green products in Nepal. Following the notion of the theory of planned behavior, this study uses a convenience sampling method to collect data using a structured questionnaire via KOBO Toolbox. The results show that environmental concern, green perceived benefits, green perceived quality, green willingness to purchase, and green future estimates all significantly impact green purchase decisions. Green marketing is an emerging concept that deserves more attention. As a result, more people are urged to adopt green goods for environmental and health reasons. Therefore, these results may help policymakers develop efficient plans and tactics to encourage sustainable consumption.